Using Virtal Machines to increase honeypot security - Piva, Eduardo Fernandes; Geus, Paulo Lício de (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2005: Anais do V Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2005.21548, 2005)
This work in progress discuss how virtual machines can be used to implement a data capture system for a honeynet. The main advantage of this approach is that the data capturing is done outside the honeypot kernel, making it practivally impossible to be detected and disabled by the intruder. By achiving this goal, a honeypot can be deployed in a safer environment, mitigating risks involved when using a honeynet.